Can we predict post-surgical improvement in functional stooping in lumbar spinal stenosis? Insights from oblique lumbar interbody fusion outcomes and radiologic predictors - Dong-Ho Kang; Jonghyuk Baek; Bong-Soon Chang; Sam Yeol Chang; Dongook Kim; Sanghyun Park; Hyoungmin Kim (BMC Musculoskeletal Disorders)
Abstract Background Functional stooping, characterized by a forward-flexed lumbar posture in patients with lumbar spinal stenosis (LSS), serves as a compensatory mechanism aimed at alleviating pain by expanding the constricted spinal canal. Surgeons widely use the oblique lateral interbody fusion (OLIF) to treat patients with LSS, restoring segmental lordosis in index surgical level. In some patients with LSS, improvement of global sagittal imbalance occurs after short-level OLIF. it remains unclear whether this is predominantly due to segmental correction or the resolution of functional stooping. Therefore, this study aimed to evaluate the effect of functional stooping resolution and segmental correction on sagittal imbalance after short-level OLIF, and identifying predictors of presence or absence of preoperative functional stooping in LSS. Methods A retrospective review was conducted on LSS patients who underwent single or two-level OLIF with preoperative C7 sagittal vertical axis (SVA) > 50 mm. The clinical and radiological factors were analyzed. Logistic regression and receiver operating characteristic curve analysis were conducted to identify factors associated with presence or abscence of preoperative functional stooping, and to establish predictive threshold values, respectively. Results A total of 103 patients with a mean age of 71.6 ± 8.6 years were included. In patients with preoperative functional stooping, segmental correction at the index surgical level contributed to only 47.7% of the total change of lumbar lordosis (LL), whereas the change of lordosis in remnant mobile lumbar segments constituted 52.3% of the total change of LL. Preoperative thoracic kyphosis (TK) (OR [95% CI]: 1.037 [1.002–1.073]), and preoperative SVA (OR [95% CI]: 0.986 [0.972–0.999]) were significant associated factors for predicting LSS patients without functional stooping. Conclusions Functional stooping resolution markedly impacts global sagittal balance correction in LSS patients following short-level OLIF. Preoperative functional stooping correlates with greater TK and reduced SVA. For patients likely to achieve functional stooping resolution, single-level surgery may suffice initially, with deformity correction reserved if needed.